Relationship between lower urinary tract symptoms and erectile function in men aged over 40 years in Brazzaville, Republic of the Congo - Ghidmar Onguélé-Okemba; Yannick Ijosdi Dimi Nyanga; Roland Bertile Banga-Mouss; Steve Aristide Ondziel Opara; Nemrod Lazarel Ekouya Oba; Anani Wencesl Severin Odzébé; Prosper Alain Bouya (Discover Medicine, 2026)
Abstract Background Lower urinary tract symptoms (LUTS) and erectile dysfunction (ED) are common conditions in men over 40 years and significantly impair quality of life. Objective To evaluate and quantify the linear relationship between LUTS and erectile function in men aged over 40 years in Brazzaville. Methods This was an analytical, prospective cross‑sectional study. Sexually active men aged over 40 years were included consecutively. LUTS were assessed using the International Prostate Symptom Score (IPSS), and erectile function was assessed using the five‑item International Index of Erectile Function (IIEF‑5). Pearson correlation tests were performed, and multivariate linear regression was used to identify an independent association between the two scores after adjustment for potential confounders. Results A total of 337 participants were included, with a mean age of 61 (SD: 8) years. LUTS were present in 93.8% of participants, mainly mild (44.2%) and moderate (40.7%). ED was reported by 76.3% of men, predominantly mild (27.9%). The IPSS was negatively correlated with the IIEF‑5 ( r = − 0.35; p < 0.001), as were all individual items (− 0.32 < r < − 0.20; p < 0.001). After multivariate adjustment, higher IPSS remained significantly associated with lower IIEF‑5 (aβ = −0.23; p < 0.001), primarily for storage symptoms (aβ = −0.14; p = 0.009). Conclusion This study demonstrates a significant and independent correlation between LUTS and erectile function in men over 40 years.